Sunteți pe pagina 1din 1

Derivatele unor funcții elementare

Funcția f 𝒇′

𝒇: ℝ → ℝ, 𝒇(𝒙) = 𝒄 𝒄′ = 𝟎

𝒇: ℝ → ℝ, 𝒇(𝒙) = ⅇ𝒙 (ⅇ𝒙 )′= ⅇ𝒙


𝒈: ℝ → ℝ, g(𝒙) = 𝒂𝒙 , 𝒄𝒖 𝒂 > 𝟎, 𝒂 ≠ 𝟏 (𝒂𝒙 )′ = 𝒂𝒙 ∗ 𝐥𝐧 𝒂

𝟏
𝒇: (𝟎, +∞) → ℝ, 𝒇(𝒙) = 𝐥𝐧 𝒙 (𝐥𝐧 𝒙)′ =
𝒙
𝟏 𝟏
𝒈: (𝟎, +∞) → ℝ, g(𝒙) = 𝐥𝐨𝐠 𝒂 𝒙 , 𝒄𝒖 𝒂 > 𝟎, 𝒂 ≠ 𝟏 (𝐥𝐨𝐠 𝒂 𝒙)′ = ⋅
𝐥𝐧 𝒂 𝒙

𝒇: ℝ → ℝ, 𝒇(𝒙) = 𝐬𝐢𝐧 𝒙 (𝐬𝐢𝐧 𝒙)′ = 𝐜𝐨𝐬 𝒙

𝒇: ℝ → ℝ, 𝒇(𝒙) = 𝐜𝐨𝐬 𝒙 (𝐜𝐨𝐬 𝒙)′ = − 𝐬𝐢𝐧 𝒙

𝒇: ℝ → ℝ, 𝒇(𝒙) = 𝒙𝜶 , 𝒄𝒖 𝜶 ∈ ℝ (𝒙𝜶 )′ = 𝜶 ∗ 𝒙𝜶−𝟏

𝝅 𝟏
𝒇: ℝ ∖ {(𝟐𝒌 + 𝟏) ⋅ |𝒌 ∈ ℤ} → ℝ, 𝒇(𝒙) = 𝐭𝐠 𝒙 (𝐭𝐠 𝒙)′ = = 𝟏 + 𝒕𝒈𝟐 𝒙
𝟐 𝒄𝒐𝒔𝟐 𝒙

𝟏
𝒇: ℝ ∖ {𝒌𝝅|𝒌 ∈ ℤ} → ℝ, 𝒇(𝒙) = 𝐜𝐭𝐠 𝒙 (𝐜𝐭𝐠 𝒙)′ = − 𝟐
= −(𝟏 + 𝒄𝒕𝒈𝟐 𝒙)
𝒔𝒊𝒏 𝒙